Economic Indicators in Integrated Reports of Selected Capital Groups - Findings of the Research - Sikacz , Hanna (Studia Oeconomica Posnaniensia, 2018)
The aim of the study is to assess the quality of the leading integrated reports published by capital groups in Poland. The main point focused on a set of economic indicators which are extracted according to the GRI guidelines. Also, in the follow up of a specific selection (detailed analyses of the content of integrated reports allow to choose some general conclusions) for the mainstream studies several integrated reports of entities aspiring as socially responsible were chosen. The results of studies using induction methods are not optimistic. The reports being prepared on the basis of the GRI guidelines do not ensure the comparability of information. Also looking at the specific details of integrated reports the quality of them is not satisfactory. If an integrated report is to be fundamental to communicate with stakeholders, the reporting standards should be mandatory and strictly defined, giving the ability to standardize information in order to improve readability and comparability of the data. Also the verification of an integrated report should be full (not only to a limited extent), so that it is possible to assess the reliability and clarity of the situation of the capital group, both in terms of financial but also the context of rights and obligations applicable to the group.